Датування мурів Печерського монастиря: аналіз та критика джерельної бази - Тараненко, С.; Кабанець, Є. (Український історичний журнал, 2019)
Мета дослідження – проаналізувати писемні та археологічні
джерела стосовно давньоруських мурів Печерського монастиря та підкреслити важливість вірного прочитання епістолії XII ст. для датування часу їх будівництва. Методологія студії спирається на принципи історизму,
системності, науковості, міждисциплінарності. Використано такі загальноісторичні методи: історіографічний аналіз, історико-генетичний, термінологічний аналіз, компаративний, типологічний. Представлено методи
датування археологічних комплексів – стратиграфічний, типологічний і
датування за аналогіями. Автори дотримуються цивілізаційного підходу й
засад культурно-інтелектуальної історії. Наукова новизна. Уперше представлено аналіз археологічних джерел щодо відкриття фортечних мурів Печерського монастиря з 1951 по 2018 рр. та відповідності адресата епістолії
Кирила Туровського «Послании некоего старца къ богоблаженному Василию
архимандриту о скиме». Висновки. Уперше мури зафіксував В.Богусевич у
1951 р., наступний етап – розкопки В.Харламова 1991–1992, С.Балакіна 2007
й С.Тараненка 2018 рр. Ці дослідження мали або рятувальний характер, або
проводилися на невеликих площах, тому наявна інформація про відкритий
комплекс вимагає перевірки та уточнень. Потребує з’ясування дата початку
будівництва мурів монастиря. Археологічні матеріали дозволяють датувати
їх зведення в межах кінця XII – початку XIII ст. Звузити цей хронологічний
проміжок може аналіз єдиної згадки про будівництво стін, що міститься
в писемному джерелі XII ст. – «Послании некоего старца къ богоблаженному
Василию архимандриту о скиме». Сьогодні існує загальноприйняте уявлення
про авторство та адресата цієї епістолії: мури могли бути зведені під час ігуменства в Печерському монастирі Василія. Проте висловлено гіпотезу, що це могло статися за часів його попередника Полікарпа. Інтерпретація адресата
листа може дати доволі вузьку дату будівництва, яку сьогодні неможливо визначити за наявними археологічними матеріалами. The purpose of the research is to analyze the written and the archaeological
sources, which contain the information on the Ancient Rus’ ramparts of
the Pechersk monastery and to underline the importance of the correct reading of the
epistle from the 12th century, that helps to find out the date of the excavated archaeological
complex of the ramparts. The methodology of research is based on the
principles of historicism and interdisciplinary approach. The following general-historical
methods are used: historiographical analysis, historical-genetic, terminological
analysis, comparative, typological. Methods of dating archaeological complexes
are used also (stratigraphic, typological and dating method by analogy). The authors
adhere to the civilizational approach and principles of cultural and intellectual history.
Academic novelty. The analysis of archaeological sources for the excavation
of the fortified walls of the Pechersk Monastery from 1951 to 2018 is presented for
the first time. An analysis of the correspondence of the recipient of the epistol Cyril of
Turov is presented. Conclusions. V.Bohusevych fixed the location of the ramparts
for the first time in 1951. The next steps were made by V.Kharlamov in 1991–1992
and by S.Balakin in 2007. But these excavations had rescue character or were made
on small area. So, the results of these researches need to be checked and itemized.
One of the things to be checked is the date of the starting point of the ramparts’ construction.
Archaeological materials allow to date the time of the ramparts’ building
widely – eve of the 12th – early 13th centuries. The right commenting of the only
mention of the ramparts in the written source of the 12th century (“The letter of one
old man to archimandrite Vasylii”) may help to make this time more specific. Today
we have the currently accepted author and addressee of this letter. They show that the
ramparts could be built during the dignity of a hegumen Vasylii. But also, the point
of view that the construction could be held during the dignity of a hegumen Polikarp
exists. The correct interpretation of the letter’s addressee could provide rather narrow
period of the walls’ building, which can not be done by archaeological methods. Such
perspective opens new possibilities for more accurate dating of some categories of
excavation findings, plinth form bricks, first of all. It may become more sustainable tool for determination of time of construction of other Ancient Rus’ monumental complexes, which could not be dated basing only on the written sources.